Material Itineraries of Electric Tuk- Tuks: The Challenges of Green Urban Development in Laos. Issue 2 (3rd April 2021) - Namba, Miki
Abstract: In the context of global climate change, development organizations aim to align their aid schemes with new environmental concerns. Since the transport sector is crucial to achieve carbon dioxide (CO2) emissions, the introduction of environmentally-friendly transportation systems and technologies to developing countries has become a major focus of development aid. This paper examines one such sustainable transport project in Laos, centering on the introduction of electric vehicles (EV). At the beginning, aid professionals envisioned the establishment of an EV network, in which batteries, hydroelectric powerplants, the CO2 market, and numerous other entities would be rolled out in the capital of Vientiane and several other towns. A few years later, it had been downscaled to introduce a small number of EVs to the World Heritage town of Luang Prabang. The article analyses this process of transformation by examining the network extensions and cuts that shaped the trajectory of the EV into Laos. It further scrutinizes how the contexts of more-or-less urban places influenced the material itineraries of the project. This process, which led to the eventual implementation of EVs in Luang Prabang, and their subsequent disappearance, provides a window of opportunity for analyzing the significant challenges of green urban development in Laos and Southeast Asia more generally.